EFEKTIVITAS KINERJA KEPALA DESA DALAM MENINGKATKAN PEMBANGUNAN DESA PAJEKO KECAMATAN MOMUNU KABUPATEN BUOL - Dunggio, Rusli (STISIPOL Mujahidin Buol, 2024)
This study aims: 1). to determine and describe the Effectiveness of Village Head Performance in Improving the Development of Pajeko Village, Momunu District, Buol Regency. The research method used is descriptive qualitative, the research location is in Pajeko Village, Momunu District, Buol Regency. Data collection techniques in the form of observation, interviews and documentation which are then analyzed using qualitative data based on the concepts of Miles and Huberman. The results of the study show that: 1. The effectiveness of the village head's performance in the construction of the Pajeko Village office is considered quite good, with the implementation of the project generally according to the planned stages. However, some challenges such as bad weather and contractor delays still hamper punctuality. Community participation in village deliberations is quite active, but it is necessary to improve project management to accelerate implementation. 2. Supervision. The effectiveness of the village head's performance in development in Pajeko Village, Buol Regency, especially in terms of supervision, is still not optimal. The village head together with the BPD (Village Consultative Body) have indeed tried to supervise the development in accordance with the RKPDes and APBDes, but supervision has not been carried out intensively. Lack of transparency in the use of the budget and less than optimal reporting reduce public trust and involvement. To increase effectiveness, further training is needed for village heads, BPD, and village officials.